McClain, Hubert (audio interview #1 of 1) - McClain, Hubert (3/6/1909 - 2/19/1994); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This interview was primarily conducted by Kaye Briegel, but Ken Naverson, a photographer who was also present., also asks some questions. The interview was conducted at McClain's home. 2/4/1981